Energy Harvest from Contaminants via Coupled Redox Fuel Cells. (May 2017) - Yang, Xu; Fan, Zheng; Zhang, Huimin; Xu, Wei; Wu, Zucheng
Abstract: Conversion of chemical energy from wastewater into electrical energy is receiving more and more attention. By selecting hydrogen-rich or nitrogen-containing pollutants as the fuels and oxidative contaminants as the oxidants, coupled redox fuel cells (CRFCs) were designed. Based on our previous work, we presented several typical fuel cells, namely the ethanol-Cr(VI), urea/urine-Cr(VI), NaBH4 -Cu(II) and NH3 -NO3 − CRFCs. Converting chemical energy in fuels and oxidants directly into electricity and achieving simultaneous detoxification of pollutants are feasible via the CRFCs. These approaches are expected to become new options for retrieving energy from pollutants.